A Low Affinity GCaMP3 Variant (GCaMPer) for Imaging the Endoplasmic Reticulum Calcium Store - Henderson, Mark J. (PLoS One, 2015)
Endoplasmic reticulum calcium homeostasis is critical for cellular functions and is disrupted in diverse pathologies including neurodegeneration and cardiovascular disease. Owing to the high concentration of calcium within the ER, studying this subcellular compartment requires tools that are optimized for these conditions. To develop a single-fluorophore genetically encoded calcium indicator for this organelle, we targeted a low affinity variant of GCaMP3 to the ER lumen (GCaMPer (10.19)). A set of viral vectors was constructed to express GCaMPer in human neuroblastoma cells, rat primary cortical neurons, and human induced pluripotent stem cell-derived cardiomyocytes. We observed dynamic changes in GCaMPer (10.19) fluorescence in response to pharmacologic manipulations of the ER calcium store. Additionally, periodic calcium efflux from the ER was observed during spontaneous beating of cardiomyocytes. GCaMPer (10.19) has utility in imaging ER calcium in living cells and providing insight into luminal calcium dynamics under physiologic and pathologic states.